Quality and process improvement of the multidisciplinary Heart Team meeting using Lean Six Sigma - Stijn Schretlen; Paulien C Hoefsmit; Ronald J M M Does; Niels J Verouden; H Reinier Zandbergen (BMJ Open Quality)
Introduction The Heart Team is a multidisciplinary meeting for shared decision-making in cardiology and cardiothoracic surgery. A quality improvement project to optimise the Heart Team was initiated after the merger of the cardiac centres of Amsterdam University Medical Centre.Methods Lean Six Sigma was applied with the purpose of improving efficiency and quality of care. Qualitative and quantitative analyses supported the multidisciplinary team during quality improvement sessions. Lean Six Sigma tools included process mapping, gemba walks, root cause analysis, line balancing, first time right, standardised work and poka-yoke.Interventions Seven areas of improvement were introduced. Key elements were the improvement of the patient referral process, introduction of a structured agenda, task division and balanced planning of patients, better exchange of information, improved availability of diagnostics and supportive tools and information technology. Work agreements were introduced to support a positive work culture and mutual respect.Results Lean Six Sigma designed an optimised Heart Team to improve efficiency by better resource utilisation, first time right decision-making, patient selection, complete and better access to information and elimination of waste. It leads to higher quality of decision-making by involving physicians in a more structured preparation, attendance of an imaging cardiologist, meeting duration within limits, installation of standard operating procedures, increased involvement of the referring cardiologists and a better engaged team.Conclusions Heart Teams are essential to make evidence-based, patient-centred treatment plans for optimal patient outcomes. However, clinical practice and experience showed that it is challenging to have an efficient and effective discussion with complete patient information and to bring together healthcare professionals. The application of Lean Six Sigma resulted in an optimised Heart Team and created a best practice design for patient-centred, evidence-based decision-making. After implementation and process stability, a postintervention analysis could clarify long-term success and sustainability.